Digital Ethnomusicological Research Data and the Institutional Repository - Hemmasi, Farzaneh; Brown, Hannah M. (MUSICultures, 2025)
As governments and funding agencies increasingly embrace Open Science and FAIR data principles, both qualitative and quantitative researchers are encouraged to deposit and share their data via institutional repositories. How suitable are repositories and data sharing for ethnomusicologists? This article chronicles a pilot project using the Canadian institutional data repository Borealis focused on digital ethnomusicological research data related to the defunct Toronto punk and metal venue Coalition TO. The article includes recommendations relating to digital ethnomusicological research data management and considerations for those contemplating storing and sharing their digital research data collections, whether via institutional repositories or other means.